2007
DOI: 10.17221/747-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Determination of water-insoluble β-D-glucan in the whole-grain cereals and pseudocereals

Abstract: Hozová B., Kuniak Ľ., Moravčíková P., Gajdošová A. (2007): Determination of water-insoluble β-d-glucan in the whole-grain cereals and pseudocereals. Czech J. Food Sci., 25: 316-324.Water-insoluble β-(1,3)-d-glucan (lichenan) was determined in 43 samples of various cereal (oats, barley, wheat, millet) and pseudocereal (buckwheat, amaranth) cultivars using a modified procedure with fungal α-amylase (Fermizyme P 300). The content of water-insoluble β-glucan varied in the dependence on the cereal species and culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…Among cereals, wheat contains low amounts of b-glucan. Hozova et al (2007) reported wheat b-glucan contents in the range of 0.47-1.4 g per 100 g. Our results exceeded these values and one RIL had a b-glucan content of 2.19 g, indicating a possibility of increasing the b-glucan content in wheat. In spite of biochemical approaches, functional genomics technologies, namely QTL analysis, genome sequencing and comparative mapping genomics, recently provided breakthroughs in the identification of components of the b-glucan system in barley.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Among cereals, wheat contains low amounts of b-glucan. Hozova et al (2007) reported wheat b-glucan contents in the range of 0.47-1.4 g per 100 g. Our results exceeded these values and one RIL had a b-glucan content of 2.19 g, indicating a possibility of increasing the b-glucan content in wheat. In spite of biochemical approaches, functional genomics technologies, namely QTL analysis, genome sequencing and comparative mapping genomics, recently provided breakthroughs in the identification of components of the b-glucan system in barley.…”
Section: Discussioncontrasting
confidence: 68%
“…b-glucans are considered undesirable in feed and malt but desirable for human nutrition. The content of b-glucan in wheat is significantly less than in barley and oats (Hozova et al 2007). QTL analysis of b-glucan was carried out only in barley and QTLs were identified on chromosomes 1H, 2H, 3H, 5H, and 7H (for review, Fincher et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…have become very popular in the human nutrition. The research has been focused on these plants because of their potential to enable the development of functional foods (Hozová et al 2007).…”
mentioning
confidence: 99%
“…Several methods of determination have been published (Hozová et al, 2007), but the choice of an appropriate extraction technique is important, because it may aff ect the quality, structure, rheological properties, molecular weight, and other functional properties of the extracted β-glucan (Ahmad et al, 2012). At present, McCleary's enzymatic method and fl ow injection analysis method are the most widely used.…”
Section: Introductionmentioning
confidence: 99%